2019
DOI: 10.1292/jvms.18-0384
|View full text |Cite
|
Sign up to set email alerts
|

Association of postpartum diseases occurring within 60 days after calving with productivity and reproductive performance in dairy cows in Fukuoka: A cow-level, retrospective cohort study

Abstract: Peripartum disorders in dairy cows negatively influence their productivity and reproductive performance. However, only a few reports have clearly indicated the influence of such disorders on the productivity and reproductive performance at a local-area or cow-level in Japan. This study aimed to elucidate the influence of diseases occurring within 60 days after calving on subsequent productivity and reproductive performance. Accordingly, a wide-area database on dairy production was used for epidemiological anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
5
0
1
Order By: Relevance
“…Metabolic and digestive disorders as well as udder disorders were more frequently stated as the reason for culling in older cows. The fact that each calving event cumulatively adds the risk of suffering postpartum diseases, such as mastitis and ketosis [33,34], might also explain this identified association.…”
Section: Culling Rates and Farmers' Stated Reasons For Cullingmentioning
confidence: 99%
“…Metabolic and digestive disorders as well as udder disorders were more frequently stated as the reason for culling in older cows. The fact that each calving event cumulatively adds the risk of suffering postpartum diseases, such as mastitis and ketosis [33,34], might also explain this identified association.…”
Section: Culling Rates and Farmers' Stated Reasons For Cullingmentioning
confidence: 99%
“…According to the USDA (2018), AMD are commonly used for treatment of mastitis and metritis in dairy cows. Goto et al (2019) reported that the percentage of cows with diseases within 60 days post-calving was 42%. The major categories of diseases were perinatal (34%), udder (18%) and metabolic (17%) diseases (Goto et al, 2019).…”
Section: Prevalence Of Enterococcus Spp/streptococcus Spp Resistance Across Seasonsmentioning
confidence: 99%
“…Goto et al (2019) reported that the percentage of cows with diseases within 60 days post-calving was 42%. The major categories of diseases were perinatal (34%), udder (18%) and metabolic (17%) diseases (Goto et al, 2019). Mastitis was the most common disease of dairy cows and the most common antibiotic treatment indication (Pol & Ruegg, 2007;Saini et al, 2012).…”
Section: Prevalence Of Enterococcus Spp/streptococcus Spp Resistance Across Seasonsmentioning
confidence: 99%
“…Metabolic and digestive disorders as well as udder disorders were more frequently stated as the reason for culling in older cows. The fact that each calving event cumulatively adds the risk of suffering postpartum diseases, such as mastitis and ketosis (40,41), might also explain this identi ed association.…”
Section: Discussionmentioning
confidence: 99%